2010
DOI: 10.1080/15401383.2010.507663
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Case Conceptualization Through Film: The Addiction Web

Abstract: Self-reflection, creativity, and experiential education are effective teaching strategies for counselor educators. Understanding and conceptualizing client cases can feel overwhelming for counselors-in-training. This article describes how the process of case conceptualization can be enhanced through the use of film. A case example is provided of how one student was able to creatively conceptualize a client through the use of film. The student's creation-The Addiction Web-is a serendipitous and visual diagram i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
(84 reference statements)
1
5
0
Order By: Relevance
“…Further, processing the films' material through class discussions and reflective journals and papers increased students' diversity awareness and sensitivity (Dave & Tandon, 2011;Laszloffy & Habekost, 2010;Loya & Cuevas, 2010;Villalba & Redmond, 2008), and helped them to process their emotional reactions and new perceptions into new professional application (Arthur & Achenbach, 2002;Whipple & Tucker, 2012). The findings from this study also corroborate the position that experiential learning methods help students develop new professional behaviors (i.e., executive skills) by improving how students observe and gather information (i.e., perceptual skills) about themselves and others, and how to make sense of clients' lived experiences with their new awareness and knowledge (i.e., conceptual skills) (Higgins & Dermer, 2002;Oh et al, 2012;Warren et al, 2010).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Further, processing the films' material through class discussions and reflective journals and papers increased students' diversity awareness and sensitivity (Dave & Tandon, 2011;Laszloffy & Habekost, 2010;Loya & Cuevas, 2010;Villalba & Redmond, 2008), and helped them to process their emotional reactions and new perceptions into new professional application (Arthur & Achenbach, 2002;Whipple & Tucker, 2012). The findings from this study also corroborate the position that experiential learning methods help students develop new professional behaviors (i.e., executive skills) by improving how students observe and gather information (i.e., perceptual skills) about themselves and others, and how to make sense of clients' lived experiences with their new awareness and knowledge (i.e., conceptual skills) (Higgins & Dermer, 2002;Oh et al, 2012;Warren et al, 2010).…”
Section: Discussionsupporting
confidence: 69%
“…The authors suggest counselor educators use class discussions to process emotions triggered by images seen in the films and guide students through the process of turning emotions and new awareness into effective counseling interventions when working with clients (Arthur & Achenbach, 2002;Dave & Tandon, 2011;Higgins & Dermer, 2002;Oh et al, 2012;Warren et al, 2010;Whipple & Tucker, 2012). This guidance models for students how counselors can help clients with the same skills in regulating emotions, synthesizing new information with previously held beliefs, and effective decision making skills aimed toward beneficial counseling outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Warren, Stech, Douglas, and Lambert (), films used as teaching tools can engage students, encourage the use of their imaginations, and help students to begin applying abstract instruction to their experience of human behavior. Higgins and Dermer () suggested that films can help students process their own reactions to novel, complicated, or challenging concepts, such as the tenets of family systems theory.…”
Section: Film‐based Pedagogy In Counselor Educationmentioning
confidence: 99%
“…Integrative models of recovery can address many factors operating within and outside of any person's life (Warren, Stech, Douglas, & Lambert, 2010). A strengths‐based, multidimensional approach is needed (Moxley & Washington, 2001; Pruett et al, 2007).…”
Section: Integrated Recoverymentioning
confidence: 99%